PENGARUH MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE JIGSAW TERHADAP HASIL BELAJAR TOLAK PELURU - Kartono, Herkulanus Andi; Triansyah, Andika; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem of this study is whether there is any influence in using the jigsaw type cooperative learning model. This study aims to find out the bullet resistance skills of students with a jigsaw type cooperative learning model in SMA N 1 Sengah Temila.This research method uses experimental methods with pre-experimental designs. The population is 254, the sample is 37. Data collection uses direct observation techniques. The instrument used is a bullet assessment instrument. Data analysis using t test analysis (influence test).Bullet results in this study showed an average pre-test 71, 62 and for the posttest average of 79, 67 increased by 8.05, based on the test of the effect of the withdrawal of the t-test value of 17.78 looking at the static table on the degrees of freedom dk = (N-1) is 37-1 = 36 significant level 5% t table value is 2,021. Thus the value of the t-test level = 17.78 is greater than 2.021, meaning that the hypothesis is accepted there is an influence of the jigsaw type cooperative learning learning model on the learning outcomes of bullet-drop at class XI students in SMA N 1 Sengah Temila. The percentage increase is 13.63%. Keywords: Jigsaw Cooperative Learning. Shot put